Dendrobium chrysotoxum Lindl. Alleviates Diabetic Retinopathy by Preventing Retinal Inflammation and Tight Junction Protein Decrease - Zengyang Yu; Chenyuan Gong; Bin Lu; Li Yang; Yuchen Sheng; Lili Ji; Zhengtao Wang (Journal of Diabetes Research)
Diabetic retinopathy (DR) is a serious complication of diabetes mellitus. This study aimed to observe the alleviation of the ethanol extract of Dendrobium chrysotoxum Lindl. (DC), a traditional Chinese herbal medicine, on DR and its engaged mechanism. After DC (30 or 300 mg/kg) was orally administrated, the breakdown of blood retinal barrier (BRB) in streptozotocin- (STZ-) induced diabetic rats was attenuated by DC. Decreased retinal mRNA expression of tight junction proteins (including occludin and claudin-1) in diabetic rats was also reversed by DC. Western blot analysis and retinal immunofluorescence staining results further confirmed that DC reversed the decreased expression of occludin and claudin-1 proteins in diabetic rats. DC reduced the increased retinal mRNA expressions of intercellular adhesion molecule-1 (ICAM-1), tumor necrosis factor α (TNFα), interleukin- (IL-) 6, and IL-1β in diabetic rats. In addition, DC alleviated the increased 1 and phosphorylated p65, IκB, and IκB kinase (IKK) in diabetic rats. DC also reduced the increased serum levels of TNFα, interferon-γ (IFN-γ), IL-6, IL-1β, IL-8, IL-12, IL-2, IL-3, and IL-10 in diabetic rats. Therefore, DC can alleviate DR by inhibiting retinal inflammation and preventing the decrease of tight junction proteins, such as occludin and claudin-1.